2019
DOI: 10.21873/anticanres.13403
|View full text |Cite
|
Sign up to set email alerts
|

CD204-Positive Tumor-associated Macrophages Relate to Malignant Transformation of Colorectal Adenoma

Abstract: Background/Aim: Colorectal adenoma is well known as a precursor lesion of colorectal adenocarcinoma (ADC). We recently reported the significance of CD204 (+) tumor-associated macrophages (TAMs), a vital component of the tumor microenvironment, in the carcinoma development of gastric adenoma. The aim of the present study was to clarify the roles of TAM in the malignant transformation of colorectal adenoma. Materials and Methods: We immunohistochemically assessed the TAM number in 88 tubular or tubulovillous ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Besides, patients with CD206+ TAM density and high CD206/CD68 ratio had significantly worse DFS and OS (124). CD204+ TAMs were abundantly detected in high-grade colorectal adenomas in comparison with low-grade adenomas that was shown immunohistochemically in 88 tubular or tubulovillous adenomas (131). In advanced colorectal cancer (stage IV), patients with a high number of peritumoral or intratumoral stabilin-1+ macrophages had a shorter DSS that was found in the Finland cohort of 159 patients.…”
Section: Negative Role Of M2-like Tams In Prognosis Of Crcmentioning
confidence: 80%
“…Besides, patients with CD206+ TAM density and high CD206/CD68 ratio had significantly worse DFS and OS (124). CD204+ TAMs were abundantly detected in high-grade colorectal adenomas in comparison with low-grade adenomas that was shown immunohistochemically in 88 tubular or tubulovillous adenomas (131). In advanced colorectal cancer (stage IV), patients with a high number of peritumoral or intratumoral stabilin-1+ macrophages had a shorter DSS that was found in the Finland cohort of 159 patients.…”
Section: Negative Role Of M2-like Tams In Prognosis Of Crcmentioning
confidence: 80%
“…In CRC, TAMs possess an intricate role, as their distribution towards the tumor might increase or hinder tumor growth [ 169 ]. High numbers of CD68+ TAMs in the invasive front were associated with favorable outcome, while other reports indicated that intratumoral CD68+ TAM counts were related with tumor penetration, lymph node metastasis and advanced stages of colorectal cancer [ 173 , 174 , 175 ]. Thus, the role of TAMs and their subsets remain to be defined.…”
Section: The Role Of P53 In the Tumor Microenvironmentmentioning
confidence: 99%
“…However, p53 was found to regulate cells of the innate immune system including TAMs. Although the underlying mechanism is unclear and needs further investigation, p53 expression in tumor cells correlated with CD204+ TAMs and density of tumor vessels in CRC [ 173 ].…”
Section: The Role Of P53 In the Tumor Microenvironmentmentioning
confidence: 99%
“…TAMs in CRC patients are associated with expansion of the microvascular bed. CD204-positive TAMs are related to the malignant transformation of colorectal adenomas ( 39 ). TAMs have been indicated to be a prognostic and predictive biomarker of stage II colon cancer in patients receiving adjuvant chemotherapy ( 40 ).…”
Section: Discussionmentioning
confidence: 99%